PENGAWASAN TIM PENGENDALI KECAMATAN DALAM PELAKSANAAN PENGGUNAAN DANA HIBAH KHUSUS OLEH MASYARAKAT DESA/KELURAHAN DI KECAMATAN BUNGARAYA KABUPATEN SIAK TAHUN 2012 - Abdul Qosyim; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Control team in the supervision of financial activities of the District a special grant for rural community groups that aim to increase community participation in accelerated development, rehabilitation and improvement of public facilities and social facilities. The programs and grants in the District Bungaraya, Siak, community participation correlation before implementation, during implementation, and after implementation. development should Siak regent meet the requirements of Regulation No. 17 Year 2010.The purpose of this study was to determine the supervision carried out by the District Steering Committee for the supervision and constraints menajadi Control Team Siak Regency Regent Regulation No. 17 Year 2010 on Guidelines Special Grant For Community Groups / District Village.Types and methods of research used in this study is descriptive. Once the data is collected peneelitian finished then compiled and classified the data and create a list of tables that have been defined by categories. Data were analyzed qualitatively described, and especially the public met with questionnaires to 50 variables related to community participation and development of environmental infrastructure is measured in Likert scale.The results showed District Monitoring Control Team Implementation Using Special Grant for Rural Communities Village On subdistrict Bungaraya Siak 2012 in category quite well. It is based on the responses of respondents who stated that districts Control Team can not fully supervise properly. despite the passage of the implementation of the development of this field. Public participation in the development environment most affect infrastructure development. Public participation during implementation has less effect in accordance with program planning. The development of the infrastructure environment through grant programs in the district through the monitoring team Bungaraya Control District has done quite well and have met regulatory requirements Siak regent No. 7 of 2010, Determination of Standards, personal review, monitoring through oral reports, surveillance through a written report, a deviation that is true.Keywords: monitoring, community participation, environmental infrastructure